Manajemen Peserta Didik dalam Pembinaan Perilaku Keberagamaan - Diantoro, Fery (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
Religious behavior becomes an important point that is very fundamental to be owned by every student, because this is closely related to the attitudes and behaviors that will be demonstrated by students in their daily life. Therefore, the schools should be able to present good behavior and religious attitudes to students. Religious behavior coaching is the process of behavior formation, morality and character for students to stock the present and future life. Behavior coaching of students into the work domain of the student management. The school must manage the students well to create students that are in accordance with what has been expected and aspired. In this study using a descriptive qualitative approach, describe the student management in the religious behavior coaching in MTs Al-Burhan Watulimo. With the findings consists of students orientation activities, the worship habituation, reading Al-Quran, scientific and Islamic studies, and guidance of discipline and character.ÙØµØ¨Ø Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙØ·Ø© ÙÙÙØ© Ø¬Ø¯Ø§ Ø£Ù ØªÙÙÙ ÙÙÙÙÙØ© ÙÙ ÙØ¨Ù ÙÙ Ø§ÙÙØªØ¹ÙÙØ ÙØ£Ù ÙØ°Ø§ ÙØ±ØªØ¨Ø· Ø§Ø±ØªØ¨Ø§Ø·Ø§ ÙØ«ÙÙØ§ Ø§ÙÙÙØ§ÙÙ ÙØ§ÙØ³ÙÙÙÙØ§Øª Ø§ÙØªÙ Ø³ÙØªÙ Ø¥Ø«Ø¨Ø§ØªÙØ§ ÙÙ ÙØ¨Ù Ø§ÙÙØªØ¹ÙÙÙÙ ÙÙ ØÙØ§ØªÙÙ Ø§ÙÙÙÙÙØ©. ÙØ°ÙÙØ ÙÙØ¨ØºÙ Ø£Ù ØªÙÙÙ Ø§ÙÙØ¯Ø±Ø³Ø© ÙØ§Ø¯Ø±Ø© Ø¹ÙÙ ØªÙØ¯ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¬ÙØ¯ ÙØ§ÙÙÙØ§ÙÙ Ø§ÙØ¯ÙÙÙØ© ÙÙÙØªØ¹ÙÙÙÙ. ØªÙØ¬ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙ Ø¹ÙÙÙØ© ØªØ´ÙÙÙ Ø§ÙØ³ÙÙÙ ÙØ§ÙØ£Ø®ÙØ§Ù ÙØ§ÙØ·Ø§Ø¨Ø¹ ÙÙÙØªØ¹ÙÙÙÙ ÙØªØ®Ø²Ù Ø§ÙØÙØ§Ø© Ø§ÙØØ§ÙÙØ© ÙØ§ÙÙØ³ØªÙØ¨ÙÙØ©. ØªÙØ¬ÙÙ Ø³ÙÙÙ Ø§ÙÙØªØ¹ÙÙÙÙ ÙÙ ÙØ¬Ø§Ù Ø¹ÙÙ Ø¥Ø¯Ø§Ø±Ø© Ø§ÙÙØªØ¹ÙÙÙÙ. ÙØ¬Ø¨ Ø¹ÙÙ Ø§ÙÙØ¯Ø±Ø³Ø© Ø¥Ø¯Ø§Ø±Ø© Ø§ÙÙØªØ¹ÙÙÙÙ Ø¨Ø´ÙÙ Ø¬ÙØ¯ ÙØ®ÙÙ Ø§ÙÙØªØ¹ÙÙÙÙ Ø§ÙØªÙ ØªØªÙØ§ÙÙ ÙØ¹ ÙØ§ ÙØ§Ù ÙØªÙÙØ¹Ø§ ÙØªØ·ÙØ¹Ø§. ÙÙ ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§Ø³ØªØ®Ø¯Ù Ø§ÙÙÙÙØ¬ Ø§ÙÙØµÙÙ Ø§ÙÙÙØ¹ÙØ ÙØµÙ Ø¥Ø¯Ø§Ø±Ø© Ø§ÙÙØªØ¹ÙÙÙÙ ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙ Ø§ÙÙØ¯Ø±Ø³Ø© Ø§ÙØ«ÙØ§ÙÙØ© "Ø§ÙØ¨Ø±ÙØ§Ù" ÙØ§ØªÙÙÙÙÙ. ÙØ¹ Ø§ÙÙØªØ§Ø¦Ø¬ Ø§ÙØªÙ ØªØªÙÙÙ ÙÙ Ø£ÙØ´Ø·Ø© ØªÙØ¬ÙÙ Ø§ÙÙØªØ¹ÙÙÙÙØ ÙØ§ÙØ¹Ø¨Ø§Ø¯Ø© Ø§ÙØªØ¹ÙØ¯Ø ÙØªØ¹Ø²ÙØ² ÙØ±Ø§Ø¡Ø© Ø§ÙÙØ±Ø¢ÙØ ÙØ¯Ø±Ø§Ø³Ø© Ø¹ÙÙÙØ© ÙØ§ÙØ¥Ø³ÙØ§ÙÙØ©Ø ÙÙØ°ÙÙ ØªØ¯Ø±ÙØ¨ Ø§ÙØ§ÙØ¶Ø¨Ø§Ø· ÙØ§ÙØ£Ø®ÙØ§Ù.